Mittelalterliche Eliten und Kulturtransfer östlich der Elbe ; interdisziplinäre Beiträge zu Archäologie und Geschichte im mittelalterlichen Ostmitteleuropa. - Klammt, Anne (2009)
The different written and archaeological sources give a very heterogeneous picture of the social and religious structures in Eastern Middle Europe. Recent developments in modern archaeological and historical research have shown new approaches to the analysis of elites. In every society there is a leading minority, who cumulates both wealth and prestige and is characterized by an elevated social rank, reputation and acceptance. An external marker of these elites is especially the superregional transfer of certain items, but also of the culturally encoded value systems. The present study asks whether this notion of cultural transfer, developed in the context of modern history, can be applied as well to the study of mutual influences between the elites of medieval Western and Eastern Middle Europe. It also raises the question if this terminology is equally useful for the analysis of written and material sources, and to what extent it might open a new perspective on the rich but as yet often unexplored history of the lands east of the Elbe river.